Beter regulation of public-private partnership for transport infrastructure: Summary and conclusions - Stephen Perkins (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
This report is based on discussions at an International Transport Forum Roundtable1 convened in September 2012 to review experience with the regulation of public private partnerships (PPPs) in the transport sector. Conclusions from the debate are developed with reference to the literature, particularly in relation to managing the risks associated with forecasting traffic. The report focuses on actuarial, structural and behavioural approaches to improving the regulation of PPPs and containing liabilities created by PPPs for public finance. It also examines the potential for private financing of infrastructure by treating packages of transport projects as regulated utilities. The report aims to clarify the objectives of PPPs, their impact on public finance and the different types of risk that need to be managed.
Keywords: 330; Verkehrsinfrastruktur; Öffentlich-private Partnerschaft; Regulierung